Primary Schools in Border Areas’ Strategies to Build Early Digital Economy Concept through The Critical Reasoning Dimension of Pelajar Pancasila Profile - Purnasari, Pebria Dheni; Sadewo, Yosua Damas; Saputro, Totok Victor Didik; Santosa, Donald Samuel Slamet; Sanoto, Herry (LPPM STKIP Kusuma Negara, 2025)
The objective of this research is to further examine the strategies used by primary schools in Bengkayang, a border area, in developing the concept of digital economy through the Pelajar Pancasila Profile in the dimension of critical reasoning. This research is an exploratory study with a qualitative approach. The research subjects consist of three primary schools in the border area with different accreditation levels: A, B, and C accreditation. Four teachers were selected from each school, making a total of 12 teacher respondents in this study. The data collection includes interviews, open questionnaires, observations, and literature review. The results of this study show that the concept of digital economy is still unstructured, which can be seen from the fact that the teaching materials used have not been constructed comprehensively. The limitations of understanding related to the concept of the digital economy in elementary schools have not been fully mastered by teachers, so it also has an impact on student understanding. Such conditions encourage the need for training, especially in designing teaching materials and assessments that can accommodate this need. In addition, schools also need to support the improvisation of teaching materials so that they do not depend on the textbooks.